2012
DOI: 10.4155/bio.12.193
|View full text |Cite
|
Sign up to set email alerts
|

A Workflow For The Metabolomic/Metabonomic Investigation of Exhaled Breath Using Thermal Desorption Gc–Ms

Abstract: This approach facilitated more efficient data modeling and a case study from a 22-participant (10 male, 12 female) stress-intervention experiment. Principal component analysis of data registered by retention indexing did not classify successfully stressed from unstressed states. By contrast, adoption of a breath matrix approach enabled 95% separation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 22 publications
0
35
0
Order By: Relevance
“…Written informed consent was obtained from participants and parents. The apparatus and workflow used in this study have been reported previously [4,15,16].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Written informed consent was obtained from participants and parents. The apparatus and workflow used in this study have been reported previously [4,15,16].…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the experimental challenge of obtaining reproducible samples from children at different stages of lung-development has not been clearly addressed. The technical challenges of reproducible and safe breath sampling have been discussed recently [4] where the use of adaptive sampling based on the continuous monitoring of the breathing patterns of a participant with the same portion of each breath sampled was emphasized. Achieving this necessitated the use of a full face mask to provide a consistent and reproducible air supply, and a consistent and reproducible sampling operation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The sampling method and analysis workflow has been described previously [12,13] Figure 1. It is important to note that the participant was supported and encouraged to remain in a quiet and relaxed state throughout the whole sampling procedure.…”
Section: Breath Sample Collectionmentioning
confidence: 99%
“…The data processing workflow adopted has been described previously [15]. Briefly, the TD-GC-MS data were deconvoluted (AnalyzerPro Spectral Works, UK), and a typical breath sample was found to contain approximately 500 resolvable compounds.…”
Section: Quality Controlmentioning
confidence: 99%